Thyroid function in women with polycystic ovary syndrome - Patidar, Bharti; Sapkal, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study aimed to assess the serum thyroid stimulating hormone (TSH) levels in women with polycystic ovary syndrome (PCOS), and its variation with obesity, insulin resistance and LH:FSH ratio. Methods: This was a facility based cross sectional study conducted for a period of 18 months on a total of 165 females with PCOS diagnosed based on Rotterdam 2003 criteria. A thorough history and clinical and anthropometric examination was conducted for all females. USG abdomen and serum TSH levels and fT4 were also done and the findings were recorded on questionnaire. Results: Subclinical hypothyroidism was documented in 17% females with PCOS. No statistically significant difference in mean values of LH:FSH ratio, insulin resistance, and obesity parameters were noted among euthyroid and subclinical hypothyroid females with PCOS (p>0.05). TSH levels in present study showed a statsitcally significant positive correlation with BMI. Conclusions: The proportions of thyroid disorders are higher in females with PCOS and they both may present with various similar clinical features. BMI in females with PCOS has significant positive correlation with TSH levels. However, it is not clear whether thyroid dysfunction has significant effect on insulin resistance.